Elbow Coronal Shear Injury Presenting as a Rare Fracture Triad Involving Capitellum, Lateral Condyle and Olecranon - A Case Report and its Pathomechanism - Kaustav Mukherjee; Sumit Sahu (Journal of Orthopaedic Case Reports)
Introduction: Coronal shear injuries are a rare subgroup of elbow fractures. Fractures involving the capitellum, lateral condyle, and olecranon are a rare triad, presenting as a result of very specific trauma mechanism and often challenging to treat. Addressing all these fragments often entails surgeons resorting to more than one approach to adequately fix the fractures. Case Report: An elderly lady presented with a history of a slip and fall at home on flexed elbow. Radiographs revealed a unique fracture pattern with involvement of capitellum, olecranon, and lateral condyle. A single standard posterior approach to elbow and dual fracture window technique was utilized to fix the fragments sequentially, with capitellum fixed in posteroanterior fashion with headless compression screw. Lateral condyle and olecranon were fixed appropriately in sequence. Initial postoperative immobilization for 2 weeks was followed by gradual elbow movements as tolerated. A good functional and radiological outcome was recorded at the end of the final follow-up. Conclusion: A single incision posterior approach, utilizing the dual fracture window, can be an effective way to fix all fracture fragments in a single approach for coronal shear elbow fractures.